2019
DOI: 10.1523/eneuro.0204-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation (tDCS) Induces Adrenergic Receptor-Dependent Microglial Morphological Changes in Mice

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 56 publications
(71 reference statements)
0
48
0
Order By: Relevance
“…Anodal tDCS actions in glia were further confirmed by Mishima et al [76]. Using a mouse model lacking Ca 2+ uptake in astrocytes, the inositol trisphosphate receptor type 2 (IP3R2) knockout (KO) mouse and also an adrenergic receptor antagonist, they confirmed decreased microglia motility along with soma enlargement in tDCS stimulated animals [76]. In poststroke recovery, it was found that anodal currents significantly increased the GAP-43 and the microtubuleassociated protein 2 (MAP-2) expression around the infarct area [56].…”
Section: Activation Of Neuroplasticity-associated Genementioning
confidence: 64%
See 2 more Smart Citations
“…Anodal tDCS actions in glia were further confirmed by Mishima et al [76]. Using a mouse model lacking Ca 2+ uptake in astrocytes, the inositol trisphosphate receptor type 2 (IP3R2) knockout (KO) mouse and also an adrenergic receptor antagonist, they confirmed decreased microglia motility along with soma enlargement in tDCS stimulated animals [76]. In poststroke recovery, it was found that anodal currents significantly increased the GAP-43 and the microtubuleassociated protein 2 (MAP-2) expression around the infarct area [56].…”
Section: Activation Of Neuroplasticity-associated Genementioning
confidence: 64%
“…It was also demonstrated that sensory evoked cortical responses were boosted after tDCS via alpha-1 adrenergic receptormediated astrocytic Ca 2+ /IP3 signaling, thus involving also glia and the adrenergic system [75]. Anodal tDCS actions in glia were further confirmed by Mishima et al [76]. Using a mouse model lacking Ca 2+ uptake in astrocytes, the inositol trisphosphate receptor type 2 (IP3R2) knockout (KO) mouse and also an adrenergic receptor antagonist, they confirmed decreased microglia motility along with soma enlargement in tDCS stimulated animals [76].…”
Section: Activation Of Neuroplasticity-associated Genementioning
confidence: 81%
See 1 more Smart Citation
“…Prolonged stimulation necessarily includes effects operating on both short timescales (membrane polarization, plasticity induction) and longer timescales (cell motility and immune responses), e.g. [81]. However, shortening the stimulation and pairing it with quicker (sub-minute) bouts of training as we have done here, could be a useful strategy to isolate effects based on Hebbian plasticity induction, which operate on faster timescales.…”
Section: Mechanismmentioning
confidence: 97%
“…Moreover, the potential effects of transcutaneous stimulation, including TI, may not be limited to neurons. For example, it has been suggested that glial cells may be affected by transcranial electric stimulation (Gellner et al, 2016;Mishima et al, 2019;Ruohonen and Karhu, 2012). Some of these phenomena have been preliminarily explored by Grossman et al, in their safety assessment of TI with no evidence of anatomical side effects (Grossman et al, 2017).…”
Section: Articlementioning
confidence: 99%